2011
DOI: 10.1103/physrevd.83.114031
|View full text |Cite
|
Sign up to set email alerts
|

Searches for thetof a fourth family

Abstract: We study the detection of the t ′ of a fourth family during the early running of LHC with 7 TeV collision energy and 1 fb −1 integrated luminosity. By use of a neural network we show that it is feasible to search for the t ′ even with a mass close to the unitarity upper bound, which is in the 500 to 600 GeV range. We also present results for the Tevatron with 10 fb −1 . In both cases the search for a fourth family quark doublet can be significantly enhanced if one incorporates the contribution that the b ′ can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Both of the neural network discriminant analysis and the boosted decision tree discriminant analysis are considered. TMVA methods have been broadly used in the top quark precision measurements by experimental collaborations [57,58,59] and W-jet substructure analysis [60], as well as new physics search studies, like Higgs boson search [61] and heavy quarks search [62,63,64]. The boost decision tree method has been adopted in the light charged Higgs boson search [65].…”
Section: Multivariate Analysis and Search Boundsmentioning
confidence: 99%
“…Both of the neural network discriminant analysis and the boosted decision tree discriminant analysis are considered. TMVA methods have been broadly used in the top quark precision measurements by experimental collaborations [57,58,59] and W-jet substructure analysis [60], as well as new physics search studies, like Higgs boson search [61] and heavy quarks search [62,63,64]. The boost decision tree method has been adopted in the light charged Higgs boson search [65].…”
Section: Multivariate Analysis and Search Boundsmentioning
confidence: 99%
“…It has been shown that, the artificial neural network (ANN) can be very powerful in determining the polarizations of W, Z bosons [21][22][23] and τ lepton [24]. The ANN approach is one of the machine learning methods, which have been widely used in HEP, and are being developed rapidly in recent years [25][26][27][28][29][30][31][32][33][34].…”
Section: Jhep09(2021)085mentioning
confidence: 99%
“…As done in works [16,17,37], in this work we have adopted two Multivariate Analysis methods: the neural network (multilayer perceptron) and the boosted decision tree.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…Another interesting work can be found in [15], where mainly using leptonic modes, Bob Holdom observed that it is difficult to use one cone to capture both boosted W boson and Top quark from b decay. For the semileptonic mode studied in [16,17], it is observed that once all physics objects (say two top quarks, two W bosons, two b quarks) can be reconstructed it is possible to extract the most crucial variables (like the mass bump of b ) to suppress the SM background to a controllable level. A thorough study for top-partner can be found in [18], where leptonic and b jet modes have been comprehensively analyzed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation